Flipped Classroom, Teaching Solution for Writing Class - Nugroho Nugroho; Dwi Rorin M Insana (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The research was designed to investigate the result of a study comparing two English writing classes of Indraprasta PGRI University student in the sixth semester of 2015/2016. There were thirty students for each class chosen randomly. The research was conducted from March to July 2016. One class was taught in a traditional way and the other using the flipped method. A test is given at the end of the treatment to detect the level of student understanding. Results of post test are compared using t-test to gauge whether the method of